LANGUAGE AND PERSPECTIVES OF MADURA TOURISM PROMOTION - Rosyida Ekawati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
Madura has various tourism destinations, ranging from tourism of natural wonders, culinary destinations, religious tourisms, arts, culture, and others. This study is intended to discuss the perspective of Madura tourism online promotion and the language used in each perspective to find the common pattern of the tourism online promotion. They are mostly presented in authenticity, strangerhood, and play perspectives, in positive ways although some are presented in negative message. The lexical aspects used are positive adjectives and superlatives to convey a very positive image of Madura tourism attractions or destinations.